2013
DOI: 10.4172/2329-9126.1000135
|View full text |Cite
|
Sign up to set email alerts
|

The Consultation in Primary Care: Physician Attributes that Influence Patients’ Satisfaction in Calabar, Nigeria

Abstract: Background: The Consultation is of immense importance in primary care. This study aimed to utilize physician attributes in the patient-care process in determining the proportion of patients who were satisfied or otherwise with the consultation at their doctor-patient interaction.Method: This was a cross-sectional descriptive study undertaken in the Family Medicine Clinic of the University of Calabar Teaching Hospital in the Niger Delta Region of Nigeria. A modified post consultation version of the General Prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…On the other hand, patients were highly satisfied with all the attributes of consultation by family physicians (mean score 4.63). The findings of this study related to patient satisfaction are comparable to a similar study from Kuwait (16), Egypt (17) and Nigeria (18). Patients are more satisfied in our study compared with the studies from Hail and Jeddah cities, where the mean score was 3.60 and 3.76 (7,19).…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, patients were highly satisfied with all the attributes of consultation by family physicians (mean score 4.63). The findings of this study related to patient satisfaction are comparable to a similar study from Kuwait (16), Egypt (17) and Nigeria (18). Patients are more satisfied in our study compared with the studies from Hail and Jeddah cities, where the mean score was 3.60 and 3.76 (7,19).…”
Section: Discussionsupporting
confidence: 83%
“…[ 25 ] showed that while 75% of a group of surveyed doctors felt they had satisfactorily communicated with their patients only 21% of the same patients reported satisfactory communication with the doctors. Okokon and Ogbonna[ 26 ] in a study in Calabar, Niger-Delta region of Nigeria, showed that the physician's attitude which most favourably influenced patients’ perception of quality of treatment given were inclusion of patients in decisions about their care and showing care and concern about their condition. Thus, the outcome in cancer patients, perhaps more than in any others, will certainly be improved when oncology practitioners improve on their communication skills.…”
Section: Discussionmentioning
confidence: 99%
“…Consultation time has been positively associated with patient satisfaction. 10 , 11 , 32 MAC receives a high number of patients and clinicians are under pressure to see as many as they can within a short period of time. This does not make it conducive to having an adequate consultation time.…”
Section: Discussionmentioning
confidence: 99%